(untitled) (Impetus, 2021)
For the World Health Organization (WHO), people have the opportunity to be physically active in four main sectors of daily life: work (especially if it involves manual activity); transportation (for example, walking or cycling to work); housework (for example, taking care of chores around the house); and free or leisure time (for example, participating in physical activities and sports) (WHO, 2002).